Spatial reasoning in the early years principles, assertions, and speculations - Davis, Brent (Routledge, 2015)
"Over the past several years, "spatial reasoning" has gained renewed prominence among mathematics educators, as spatial skills are proving to be a predictor of not just mathematics achievement, but future success in science, technology, and engineering. Through a careful blend of theory and practice, Spatial Reasoning in the Early Years helps define spatial reasoning and provides compelling evidence of the need for a clear focus within early education specifically. Expert educational researchers examine the theories and practices underlying contemporary school mathematics pedagogy and identify the areas of future research necessary to bringing a stronger spatial reasoning emphasis into the classroom. Each chapter is framed by classroom- or workshop-based vignettes, highlighting the complexity of spatial reasoning in educational practice. "Yet to be Answered Questions," throughout the text serve both to summarize the main content of the sections and to set the stage for subsequent chapters. The book concludes with a forward-looking agenda that contributes to developing a greater understanding of the role spatial reasoning plays in educational contexts and beyond. Supported by plentiful visual representations, Spatial Reasoning in the Early Years skillfully integrates the conceptual and the pragmatic, making this text a dynamic and accessible resource."-- Provided by publisher.